Accessory Toxins of Vibrio Pathogens and Their Role in Epithelial Disruption During Infection - Pérez-Reytor, Diliana; Jaña, Victor; Pavez, Leonardo; Navarrete, Paola; García, Katherine (Frontiers in Microbiology, 2018)
Gastrointestinal episodes associated with Vibrio species have been rising worldwide in the last few years. Consequently, it is important to comprehend how occurs the production of diarrhea, to establish new preventive and therapeutic measures. Besides the classical CT and TCP toxins, Zot, RTX and Ace among others have been deeply studied in V. cholerae. However, in other Vibrio species of clinical interest, where some of these toxins have been reported, there is practically no information. Zot activates a cascade of signals inside of the cell that increase the permeability of epithelial barrier, while RTX causes depolymerization of the actin cytoskeleton and Ace increases the permeability of intestinal cell monolayers. The goal of this study is to acquire information about the distribution of these toxins in human pathogenic Vibrios and to review the progress in the study of their role in the intestinal epithelium during infection.